The effect of bilirubin on the Fc receptor expression and phagocytic activity of mouse peritoneal macrophages - Vĕtvicka, V; Miler, I; Síma, P; Táborský, L; Fornůsek, L (Folia microbiologica, 1985)
The effect of bilirubin on the phagocytic activity of mouse peritoneal macrophages and on the expression of Fc receptors and receptors for SRBC was studied. Intraperitoneally administered bilirubin influenced the expression of Fc receptors for IgM, IgG2B, IgA and IgE, whereas the expression of other receptors as well as the phagocytic activity of peritoneal macrophages remained unchanged. The possible mechanism of the effect of bilirubin on Fc receptors is discussed.
Keywords: myši; makrofágy; Macrophages; bilirubin; Rosette Formation; receptory Fc; tvorba rozet; Mice, Inbred BALB C; zvířata; Mice; Phagocytosis; Receptors, Fc; Bilirubin; myši inbrední BALB C; fagocytóza; Animals